Criminalisation of Beggars: the Causes and Consequences of the Phenomenon (Contemporary Central & East European Law, 2020)
All authorities desire to control various aspects of their subjects’ lives. Those in power claim to do it in the name of protecting the peace and safety of all citizens. For one of groups perceived to be the most dangerous is the one whose members evade formal or informal social control – they do not work, do not have a family or are estranged from them, they have no permanent home. Therefore, to make sure that no one is out of the reach of governmental control, criminal law is utilised against them and whole ways of life, and the everyday behaviours of vagrants and homeless people began to be criminalised. And this process is still ongoing. The law thus punishes a person for their personal identity, and not for specific improper or harmful behaviour undertaken by them. In this paper I would like to analyse the problem of criminalisation of beggars throughout Polish history, and present how it impacted (and still impacts) upon the lives of the poorest and the most excluded parts of Polish society.